Analysing the need to regulate non-profit foundations under the Trustees (incorporation) Act 1952: towards transparency and good governance - Ali, Zuraidah; Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah (Universiti Malaysia Sarawak, 2020)
The establishment of any non-profit organisations in Malaysia under the Trustees(Incorporation) Act 1952empowers the Legal Affairs Division at the Prime Minister’s Department to issue a licence to enable a charitable trust fund to be created as a foundation. The foundation is authorize to collect funds from the public and obtain tax exemption from the Inland Revenue Board. The main problem is the Legal Affairs Division is not given the full authority to act as the main regulator in order to ensure that all activities and funds collected and donated are used solely for charitable purposes. What more in the modern advancement of digital technology, the lack in the method of monitoring should not be an issue. Through doctrinal and legal study and content analysis, this paper analyses the important provisions under the Trustees(Incorporation) Act 1952, by highlighting the present practices involving the establishment of a foundation under this Act and the need for further improvement in order to enhance the integrity and public confidence in donating for charitable purposes. There is also a need to explore and analyse to what extent the State Islamic Religious Authority have a role in regulating waqf foundations in Malaysia. Simultaneously, some comparative analysis on the practices of regulating charitable organizations in England and Wales arehighlighted.This article is aimsto highlight the importance of having a single regulator in Malaysia, in form of a commission, in order to regulate all matters relating charity in Malaysia.